2020
DOI: 10.1016/j.future.2019.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Towards automated feature engineering for credit card fraud detection using multi-perspective HMMs

Abstract: Machine learning and data mining techniques have been used extensively in order to detect credit card frauds. However, most studies consider credit card transactions as isolated events and not as a sequence of transactions.In this framework, we model a sequence of credit card transactions from three different perspectives, namely (i) The sequence contains or doesn't contain a fraud (ii) The sequence is obtained by fixing the cardholder or the payment terminal (iii) It is a sequence of spent amount or of elapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…At the same time, insufficient attention is paid to the accompanying efficiency factors, namely the costs of various resources (temporal, human, financial, computational). It is particularly important to reduce the time spent on the development and maintenance of systems for identifying fraudulent transactions, a factor that only [13] pays attention to.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…At the same time, insufficient attention is paid to the accompanying efficiency factors, namely the costs of various resources (temporal, human, financial, computational). It is particularly important to reduce the time spent on the development and maintenance of systems for identifying fraudulent transactions, a factor that only [13] pays attention to.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…As it could be guessed, credit card transactions are not independent events that are isolated; instead, they are a sequence of transactions [10]. Lucas et al take this property into account and create Hidden Markov Model (HMM) to map a current transaction to its previous transactions, extract derived features, and use those features to come up with a Random Forest classifier for fraud detection [10]. The features created by HMM quantify how similar a sequence is to a past sequence of a cardholder or terminal [10].…”
Section: Akila Et Al Present An Ensemble Model Named Riskmentioning
confidence: 99%
“…Lucas et al take this property into account and create Hidden Markov Model (HMM) to map a current transaction to its previous transactions, extract derived features, and use those features to come up with a Random Forest classifier for fraud detection [10]. The features created by HMM quantify how similar a sequence is to a past sequence of a cardholder or terminal [10]. They evaluate the final model using Precision-Recall AUC metric and showed that feature engineering with HMM presents an acceptable rise in the PR-AUC score.…”
Section: Akila Et Al Present An Ensemble Model Named Riskmentioning
confidence: 99%
“…Feature engineering strategies perform the exam same process. A feature engineering based model for detecting frauds in credit card transactions was proposed by Lucas et al [8]. This work aims at using HMM for the prediction process.…”
Section: Literature Reviewmentioning
confidence: 99%